Efektivitas Pembelajaran Pendidikan Kewarganegaraan Berbasis Proyek dalam Meningkatkan Nilai-Nilai TIDAR di Lingkungan Kampus - Widiyanto, Delfiyan; Wahyono, Hari; Novitasari, Novitasari; Istiqomah, Annisa; Prasetyo, Riyan (Universitas Tidar, 2024)
The purpose of this study was to determine the improvement of students' attitude aspects after taking project-based Citizenship Education courses. Citizenship Education aims to form good citizens and have ideal young citizen skills. As a form of improving the skills of young citizens with education in a formal environment, it has a greater impact on the internalization of values. This study uses a quasi-experimental research type (quasi-experimental design). This study uses a quasi-experimental design without a control or comparison class. The experimental design used is one group pre-test-post-test. The results of the study show that project-based learning can improve attitudes towards Tidar values. These values are in the form of tough, integrative, dedicated, active, and responsive values. Students' responses to project-based learning are easy and they really like the learning that is carried out. However, the improvement in attitudes towards Tidar values has not been maximized in all indicators, especially in tough and active values. In order to be able to increase all values to the maximum, a more comprehensive project learning evaluation needs to be carried out.